Pemanfaatan Limbah Kayu Untuk Seni Ukir Dan Cenderamata Di Malinau, Kalimantan Timur - Drs. Sunarto, M.Hum (Mitra SENI, 2006)
Using up wood due to the renewable lease of the woods has resulted in the abundance ofwaste of wood. Workshop on woodcarving and souvenir made of waste of wood as raw material was held and attended by participant from all regions of the district of Malinau. Using waste of wood to good advantage will give added value and will improve the welfare of the society.